FINNISH-ENGLISH PHONETICS AND PHONOLOGY - Sajavaara, Kari; Dufva, Hannele (International Journal of English Studies, 2001)
This paper first gives a summary of the theoretical approaches to the role of phonetics and phonology in language learning and teaching as developed by the Finnish-English Cross-Language Project at the University of Jyvtkkyla. In the Finnish project, the analysis was extended over the the chains of connected speech to deal with all the phenomena that give them their rhythm in speech. The project did not find it sufficient to produce simple one-to-one equations between the best structural descriptions of the two languages because many of learners’ difficulties in pronunciation cannot be assigned to phoneme paradigms. The paper also includes a survey of the findings of Finnish-English contrastive phonetics and phonology, and a description of potential sources of difficulties in Finns’ pronunciation of English.